DESIGN OF VACUUM CLEANER DUAL MODE ROBOT PROTOTYPE BASED ON ARDUINO UNO WITH BLUETOOTH AND SMARTPHONE COMMUNICATION - E.S. RAHAYU; MARDIONO; D. A. AZIS (International Journal of Innovations in Engineering Research and Technology, 2021)
Design of prototype robot vacuum cleaner based on Arduino Uno aims to produce a prototype robot that has the ability as a tool to clean house floor vacuum cleaners quickly and efficiently. Robot Vacuum Cleaner is designed as a vacuum cleaner and dirt on the floor of a room, which is operated using dual mode that is automatically and manually. Automatic mode on the robot vacuum cleaner will cause the robot to move randomly on the floor of a room and automatically avoid obstacles that are in front of the robot. Whereas in manual mode the robot vacuum cleaner moves following commands that are controlled by the user via an Android-based smartphone using the Bluetooth HC-05 communication module. SharpGP sensor mounted on the robot functioned as a sensor to avoid obstacles when cleaning the floor of the house. The program flow begins by connecting the Android Smartphone to the Bluetooth HC-05 module, then Arduino will read the input data of the mode selected by the user, which is automatic or manual mode. If automatic mode is selected, Arduino will initialize the SharpGP proximity sensor to detect the distance of objects in front of the robot and activate the vacuum motor. If the distance of the object in front of the robot robot more than 8 cm the robot will stop and turn directions to avoid the object. If the user chooses manual mode, the robot will wait for the user’s command to maneuver and activate the controlled vacuum motor using the application on the user’s smartphone. The prototype robot vacuum cleaner, which operates in dual mode, was designed using Arduino Uno as the control center, has a SharpGP proximity sensor input, Bluetooth HC-05 module and an output in the form of a DC Motor Driver IC L298N to regulate the robot’s movements and IRF520 MOSFET IC to regulate the speed of the Vacuum motor. The proximity sensor in the robot vacuum cleaner design has a detection range of 4 cm to 25 cm. This robot vacuum cleaner design can run automatically and can avoid the obstacle which is ? 6.5 cm in front of the robot. The results of distance sensor testing (Sharp GP2Y0A41SK0F) on the left side have an average error value of 0.385 cm and the proximity sensor (Sharp GP2Y0A41SK0F) on the right side has an average error value of 0.321 cm. Tests are also carried out to ensure the ability of robot movement through the floor with a slope of 15o , 20o and 25o . From the test results, the robot is not able to move at slopes greater than 25o .